The effects of the moisture content of laminated veneer lumber on bending strength and deformation determination via two-dimensional digital image correlation - Sözen, Eser; Kayahan, Kadir; Bardak, Timuçin; Bardak, Selahattin; Bardak, Timuçin; Kayahan, Kadir; Sözen, Eser (Sage Publications Ltd, 2021)
This study determined the bending strength values of laminated veneer lumber (LVL) made with beech (Fagus orientalis L.) veneer obtained by the peeling process and having four different moisture content values (0%/oven dry, 12%, 18%, and 25%). Bending tests were carried out in two different ways, i.e., for the flatwise and edgewise aspects of the LVL. Strain maps were created using two-dimensional digital image correlation (2 D DIC) and the samples having different moisture contents were compared. At the same time, the amount of displacement of the samples during the bending test was determined via conventional and DIC methods. Results of the study determined that the moisture content was effective in bending strength and tension zones. It was observed that increasing moisture content created homogeneous distribution of deformation. It was also observed that the data obtained by the 2 D DIC method were compatible with those obtained by the conventional method.
Keywords: Laminated Veneer Lumber; Two-Dimensional Digital Image Correlation; Moisture Content; Mechanical Properties; Bending Strength